2022
DOI: 10.3389/fnut.2022.925846
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Lipidomics in the Modern Meat Industry: Quality Traceability, Processing Requirement, and Health Concerns

Abstract: Over the latest decade, lipidomics has been extensively developed to give robust strength to the qualitative and quantitative information of lipid molecules derived from physiological animal tissues and edible muscle foods. The main lipidomics analytical platforms include mass spectrometry (MS) and nuclear magnetic resonance (NMR), where MS-based approaches [e.g., “shotgun lipidomics,” ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS), matrix-assisted laser desorption and ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…There are also forensic studies available [ 42 ] where the age of a fingerprint (in particular, the lipids within a fingerprint) can be determined by the O 3 -induced oxidation of TAG subsequent to ozonolysis [ 43 ]. The considerable relevance of MS-based lipidomics, including MALDI-TOF MS approaches in the meat industry, has been recently emphasized and comprehensively reviewed [ 44 ]. Recently, there have been strong efforts to obtain energy and fuel from algae (“renewable primary products”).…”
Section: Which Matrix Is Most Suitable For Individual Lipid Classes?mentioning
confidence: 99%
“…There are also forensic studies available [ 42 ] where the age of a fingerprint (in particular, the lipids within a fingerprint) can be determined by the O 3 -induced oxidation of TAG subsequent to ozonolysis [ 43 ]. The considerable relevance of MS-based lipidomics, including MALDI-TOF MS approaches in the meat industry, has been recently emphasized and comprehensively reviewed [ 44 ]. Recently, there have been strong efforts to obtain energy and fuel from algae (“renewable primary products”).…”
Section: Which Matrix Is Most Suitable For Individual Lipid Classes?mentioning
confidence: 99%
“…15 Lipidomics is a branch of metabolomics in which multiple techniques are used to quantify hundreds of chemically distinct lipids and identify potential lipid biomarkers at the molecular level. [16][17][18] By using lipidomics, Sarnyai et al suggested that EA and TVA induced a stress response and cell damage in HepG2 cells by increasing the levels of ceramide (Cer) and diglyceride (DG), and this further supported the role of DG and Cer accumulation in metabolic diseases. 3 Hepatic steatosis, non-alcoholic steatohepatitis (NASH) and liver fibrosis are the three stages of increasing severity in NAFLD, which can even deteriorate toward cirrhosis and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 96%
“…Lipidomic analysis has also been applied to estimate the impact of animal feeding methods on meat and egg quality [ 12 ]. Feed intervention can greatly alter the lipid content of eggs and meat, thus improving the nutritional value and health benefits of the products.…”
Section: Introductionmentioning
confidence: 99%